From Tragedy to Renaissance : Improving Agricultural Data for Better Policies - Carletto, Gero; Jolliffe, Dean; Banerjee, Raka (World Bank Group, Washington, DC, 2015)
Agricultural development is an essential engine of growth and poverty reduction, yet agricultural data suffer from poor quality and narrow sectoral focus. There are several reasons for this: (i) difficult-to-measure smallholder agriculture is prevalent in poor countries, (ii) agricultural data are collected with little coordination across ministries of agriculture and national statistics offices, and (iii) poor analysis undermines the demand for high-quality data. This paper argues that initiatives like the Global Strategy to Improve Agricultural and Rural Statistics bode well for the future. Moving from Devarajan's statistical "tragedy" to Kiregyera's statistical "renaissance" will take a continued long-term effort by individual countries and development partners.